The Spectrum of ACAN Gene Mutations in a Selected Chinese Cohort of Short Stature: Genotype-Phenotype Correlation - Wu, Su; Wang, Chunli; Cao, Qing; Zhu, Ziyang; Liu, Qianqi; Gu, Xinyan; Zheng, Bixia; Zhou, Wei; Jia, Zhanjun; Gu, Wei; Li, Xiaonan (Frontiers in Genetics, 2022)
Objective Mutations in the ACAN gene have been reported to cause short stature. However, the prevalence estimates of pathogenic ACAN variants in individuals with short stature vary, and the correlation between ACAN genotype and clinical phenotype remain to be evaluated. To determine the prevalence of ACAN variants among Chinese people with short stature and analyze the relationship between genotype and main clinical manifestations of short stature and advanced bone age among patients with ACAN variants. Methods We performed next-generation sequencing-based genetic analyses on 442 individuals with short stature. ACAN variants were summarized, previously reported cases were retrospectively analyzed, and an association analysis between genotype and phenotype was conducted. Result We identified 15 novel and two recurrent ACAN gene variants in 16 different pedigrees that included index patients with short stature. Among the patients with ACAN variants, 12 of 18 had advanced bone age and 7 of 18 received growth hormone therapy, 5 (71.4%) of whom exhibited variable levels of height standard deviation score improvement. Further analysis showed that patients with ACAN truncating variants had shorter height standard deviation scores (P=0.0001) and larger bone age–chronological age values (P=0.0464). Moreover, patients in this Asian population had a smaller mean bone age–chronological age value than those that have been determined in European and American populations (P=0.0033). Conclusion: Our data suggest that ACAN mutation is a common cause of short stature in China, especially among patients with a family history of short stature but also among those who were born short for their gestational age without a family history. Patients with truncating variants were shorter in height and had more obvious advanced bone age, and the proportion of patients with advanced bone age was lower in this Asian population than in Europe and America.